THE RENDERING OF FREGE’S „BEDEUTUNG“ AS „REIKŠMĖ“ AND AS „NURODYMAS“ - Plėšnys, Albinas A.; Šaulauskas, Marius Povilas (Problemos, 2017)
This article deals with the problems of understanding and translating the term Bedeutung as introduced by Gottlob Frege, which arose in the analytic tradition of philosophy of English-speaking world, and with their solutions in the context of Lithuanian philosophical terminology. Two different approaches in the translation of the term should be distinguished: literal, which pays the biggest importance to the lexical properties of the word within the context of the natural source language, and interpretive. Both approaches emerge at the crossroad of contemporary problems in philosophy of language, mind and science, and choice of one over another demonstrates rather methodological attitude than possible defects in one’s translation technique. Thus the development of Lithuanian analytic philosophy is hardly imaginable without the corresponding equivalents in Lithuanian language at hand. Literal translation of Bedeutung as reikšmė satisfies the needs for being used in both such contexts, where literal English translations, such as meaning or significance of word Bedeutung are used, and where the traditional diachronic standpoint of historiography of philosophy is held. Admitting that the vast majority of texts in contemporary analytic philosophy are written in English we suggest adding a new notion to the Lithuanian philosophical terminology, namely nurodymas, as a way to avoid conceptual difficulties and problematic usage of word referencija.